Prothrombin Time role in Head Injury & Intracranial Hematomas, A prospective Study of 325 cases - Al Atraqchi, Ahmed A Salam; Abdul Gafour, Eman (AL-Kindy College Medical Journal, 2012)
Objective: Aimed to asses the role of PT estimation in early diagnosis and predicting the extent and the outcome of head injury with ICerH and/ or ContusionMethod :PT was measured by Digiclot 818Group –1: One hundred consecutive head injured patients admitted at Neurosurgical and Al Ramadi teaching hospitals were initially estimated for prothrombin time and subsequently scannedGroup-2 : Two hundred twenty five consecutive non scanned head injured patients admitted to Neurosurgical and Al Ramadi teaching hospitals were estimated with prothrombin time at the time of insult and subsequently for the next two weeks Al – Kindy Col Med J 2012; Vol. 8 No. 1 P: 54Clinical and neurological evaluation (GCS) score in addition to computerized tomography scan was done for both groupsResult :Group -1: Twenty eight (28%) of the initially estimated head injured patients had prolonged prothrombin time in which their subsequent CT scan revealed an ICer H and/or contusionSeventy six (76%) percent of those with severely head injured patients (GCS≤8) were having an initial prothrombin time prolongation..While those with mild head injury (GCS≥12) only thirty (30%) of them were having the initial prothrombin time prolongationGroup-2 Those patients who survived the initial insult and subsequently thereafter (surgically or conservatively treated) even with a deficit.. Daily estimation of prothrombin time showed a decline within the 7-14 daysThose patients who finally died (surgically or conservatively treated) daily estimation of prothrombin time showed a persistent elevation or a fluctuation within the next 7-14 dayConclusion Prothrmbin time is an importantparameter in :1-Reflecting the severity of head injury (GCS)3-Early detection of ICerH and /or contusion2-Prognostic value in cases of of ICerH and /or contusionAbb : ICerH = Intracerebral hematomas,SDH=subdural hematomas,EDH=epidural hematomas,SAH=subarachnoid hemorrhages,PT=Prothrombin time,Pts=Patients,CT scan=computarized tomography.